2022
DOI: 10.3390/buildings12030362
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Interoperable Approach for Modelling and Managing Smart Building Data: The Case of the CESI Smart Building Demonstrator

Abstract: Buildings have a significant impact on energy consumption and carbon emissions. Smart buildings are deemed to play a crucial role in improving the energy performance of buildings and cities. Managing a smart building requires the modelling of data concerning smart systems and components. While there is a significant amount of research on optimising building energy using the smart building concept, there is a dearth of studies investigating the modelling and management of smart systems’ data, which is the start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…The findings from RQ4, designed to uncover the advantages and challenges associated with the implemented processes, are consolidated and elaborated upon in the discussion section. [8], [9], [11], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43] (2) Construction [3], [5], [15], [38], [41], [42], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59],…”
Section: Data Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…The findings from RQ4, designed to uncover the advantages and challenges associated with the implemented processes, are consolidated and elaborated upon in the discussion section. [8], [9], [11], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43] (2) Construction [3], [5], [15], [38], [41], [42], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59],…”
Section: Data Synthesismentioning
confidence: 99%
“…Smart Buildings [7], [11], [13], [22], [23], [24], [27], [33], [83], [84], [85], [86], [34], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99] As-built BIM [6], [20], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82]…”
Section: Data Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The authors analyzed the advantages of Open BIM in data and information management, emphasizing how the adoption of this approach can improve data quality, collaboration between the various actors in the infrastructure sector, and the efficiency of information management. Emphasizing the importance of obviating the loss of information, the case study conducted at the CESI Campus in Paris-Nanterre, for the realization of an intelligent building, demonstrated that IFC-based Open BIM allows for proper modeling without data loss [59]. Concerning the improvement and control of quality during the design phase, a study conducted by Häußler and Borrmann [60] proposed a standardized method to validate design quality by means of fourteen quality parameters.…”
Section: Implementation Of Open I-bim and Ifcmentioning
confidence: 99%